2021
DOI: 10.1109/access.2021.3071716
|View full text |Cite
|
Sign up to set email alerts
|

On the Partition Dimension of Tri-Hexagonal α-Boron Nanotube

Abstract: The production of low-cost, small in size, and high in efficiency objects is the topic of research in almost all scientific fields, especially of engineering. In this scenario, nanotechnology becomes of great importance. To achieve these tasks, one needs to study the different physical and chemical aspects of a chemical compound. In mathematical graph theory, chemical compounds are transformed in a unique mathematical representation and then examined under various parameters for these purposes. The Partition D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…When the specific values of moving parameters C 1 = C 2 = C 3 = 3, kekule is a part of hollow coronoid [35]. A pericondensed benzenoids structure which is known as circumcoronene also among the family of hollow coronoids [36]. A hollow coronoid, as depicted in Figure 1, had total 6 facets C 1 , C 2 , C 3 , C 4 , C 5 , C 6 .…”
Section: Construction Of Hollow Coronoidmentioning
confidence: 99%
“…When the specific values of moving parameters C 1 = C 2 = C 3 = 3, kekule is a part of hollow coronoid [35]. A pericondensed benzenoids structure which is known as circumcoronene also among the family of hollow coronoids [36]. A hollow coronoid, as depicted in Figure 1, had total 6 facets C 1 , C 2 , C 3 , C 4 , C 5 , C 6 .…”
Section: Construction Of Hollow Coronoidmentioning
confidence: 99%
“…Some chemical compounds linked to wheel graphs, and also a comparison of metric and edge metric dimensions is discussed in [31]. Adding more to it, a few interesting studies related to metric dimension can be found in [32]- [36]. More related topics are discussed in [37]- [41].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of pd( ) for numerous classes of graphs has discussed extensively in literature. For instance, the PD of starphene graph was evaluated by Ahmad et al (see [3]), bridge graph by Amrullah et al (see [4]) and of tri-hexagonal α-boron nanotube by Ayesha et al (see [30]). The bounds on PD of generalized Mobius ladder were provided by Hussain et al (see [19]) and PD for certain classes of series parallel graph was studied by Monica et al (see [23]).…”
Section: Introduction and Basic Terminologiesmentioning
confidence: 99%